Comparison of marginal fit of zirconia crown with digital and conventional impression - Deni Amalia Ningrum; Ratna Sari Dewi (Indonesia Prosthodontic Association, 2023)
Marginal fit is an important measure of the quality and clinical success of a fixed restoration. Different types of im-pression materials and techniques used can affect the marginal fit of the restoration. Conventional impression pro-cedures have long been performed by dentist to duplicate patient’s oral cavity, but this impression technique has several disadvantages. Currently, along with the development of the era of dental treatment, it is moving towards digital technology. Technological advances in dentistry today are able to eliminate the shortcomings of convention-al impression. The purpose of this review was to evaluate the marginal fit of CAD/CAM fabricated zirconia restora-tion produced via conventional and digital impression techniques. It is concluded that intraoral scanner can be used instead of conventional impression procedures in denture fabrication. Many studies show that digital impression can replace conventional impression which is still widely used. The use of various types of intraoral examination tools and various systems used can give different results.